Facile fabrication of core-shell Ni3Se2/Ni nanofoams composites for lithium ion battery anodes. (1st February 2020) - Wang, Zhongren; Gao, Quanbin; Lv, Peng; Li, Xiuwan; Wang, Xinghui; Qu, Baihua
Abstract: Due to the highly porous structure, large specific surface area, and 3D interconnected metal conductive network, nanoporous metal foams have attracted a lot of attention in the field of energy conversion and storage, especially lithium-ion batteries, which are ideal for current collectors. In this work, we develop a facile approach to fabricate core-shell Ni3 Se2 /Ni nanofoams composites. The Ni3 Se2 /Ni composites make full use of both the advantages of metal conductive network and core-shell structure, resulting in a high capacity and superior rate performance. In addition, the composites can be directly converted into electrode by a simple mechanical compression, which is more convenient than traditional casting method. What's more, this material and its structure can be extended to other devices in the field of energy conversion and storage.